Rekonstruksi Model Pembelajaran Eksegesis Yunani Berbasis Hermeneutik Formatif : Integrasi Analisis Sintaksis dan Transformasi Spiritual Mahasiswa Teologi - Anita Mariana Parulian (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2026)
This study aims to reconstruct a Greek Exegesis learning model based on formative hermeneutics by integrating syntactic analysis with the spiritual transformation of theology students. Traditional Greek instruction often emphasizes technical grammar and textual translation, thereby creating a gap between academic rigor, interpretive sensitivity, and spiritual formation. To address this issue, the present research develops and evaluates an instructional model that positions grammatical inquiry not merely as a linguistic exercise, but as a formative process for understanding Scripture responsibly. This research employs a quantitative descriptive-correlational design involving 30 theology students as participants. Data were collected through syntactic analysis tests and Likert-scale instruments measuring hermeneutical awareness and spiritual disposition. The results show that the implementation of the formative hermeneutical model achieved a high effectiveness level of 81.7%. Students’ syntactic competence reached 78%, which falls into the good category, while spiritual transformation attained 84.8%, categorized as very good. These findings indicate that the model significantly improves both analytical competence and spiritual development. This study proposes an integrative pedagogical framework in which syntactic analysis functions as a formative hermeneutical practice that shapes theological virtues, interpretive responsibility, faith maturity, and holistic ministerial readiness among theology students within diverse contemporary theological education contexts and ministries.